Inertial measurement data collection for beamforming on a moving platform - Crkvenjas, Ana (My University, 2025)
This project demonstrates how to maintain the beam of a wireless antenna system in the right direction while moving. Beamforming typically performs best when the antenna is stationary. However, for an antenna mounted on something like a drone or a car, it tends to tilt and rotate, which can disturb the signal. We solve this by measuring how the antenna moves its roll, pitch, and yaw using a small sensor called a 9-DoF IMU (nine degrees of freedom inertial measurement unit), which for the record includes an accelerometer and a gyroscope. Then we use a filter to combine these data and determine the exact orientation of the antenna at each moment. With that information, we update the direction of the signal (beam) so that it stays pointed at the target, even while the platform is moving. We tested this using a computer simulation that shows how the signal beam behaves in 2D (two dimensions) and 3D (three dimensions). The results show that the use of IMU data helps the antenna system maintain a strong and accurate signal, even during motion.
Keywords: Beamforming, wireless antenna, tilt, rotate, roll, pitch, yaw, intertial measurement unit